Factors Influencing The Stunting Incidence Of Children Aged 6 – 2 Years At The Tanah Merah Health Center, Boven Digoel District Papua Province Period 13 April – 13 May 2023 - Maria Bumarop, Ana; Rismayanti, Tetin (International Journal of Health and Pharmaceutical (IJHP), 2024)
Short term stunting can affect mental abilities and unoptimally learning, low academic achievement, developmental delays, decreased immune function, decreased cognitive function, and disorders of the burning system. Various ways are carried out so that long-term effects can be prevented and handled appropriately. Based on the foregoing then researchers are interested in conducting research with the title Factors related to Stunting Incidents in children aged 6-2 years at the Tanah Merah Health Center, Boven Digoel Regency, Papua Province, April 13 - May 13, 2023. Knowing what factors are related to the incident Stunting in children aged 6-2 years at the Tanah Merah Health Center, Boven Digoel Regency, Papua Province, April 13 - May 13, 2023.The type of research used is descriptive analytic research carried out using cross sectional methods with univariate and bivariate data analysiswith the help of the computer program SPSS version 20.Statistical test results obtained p value = 0.464, it can be concluded that there is no relationship between the incidence of shunting in children aged 6-2 years with the age of the mother and the OR 2.500 results which can be concluded that the age of the mother is 2.5 times influencing the incidence of stunting in children aged 6- 2 years. statistical test results obtained p value = 0.151, it can be concluded that there is no relation between the incidence of shunting in children aged 6-2 years and the mother's education. Statistical test results obtained p value = 0.431, it can be concluded that there is no relationship between the incidence of shunting in children aged 6-2 years with exclusive breastfeeding and the OR results of 0.556 which can be concluded that exclusive breastfeeding 0.5 times affects the incidence of shunting in children aged 6- 2 years. Statistical test results obtained p value = 0,Expected factorsthat affect eventsStunting in children aged 6-2 years can be used as a guideline in preventing stunting in the future.